ANALISIS RESEPSI MASYARAKAT TERHADAP BERITA COVID-19 DI MEDIA BATARA POS DESA JALAJJA KECAMATAN BURAU KABUPATEN LUWU TIMUR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The main problems in this study are 1) How the public's acceptance of covid-19 news by Batara pos media in Jalajja village, Burau district, East Luwu regency. 2) What is the attitude of the community towards covid-19 news from Batara pos media in Jalajja village? The type of research carried out in this study is a type of qualitative description field research, while the climbing used in this study is to use a theoretical approach to the reception and the attitude of the data source used is primary data, namely the results of interviews conducted in Jalajja village, while secondary data are sources in the form of books, journals, and theses. The data collection methods carried out are interviews, observations, and documentation. The results of this study show that: 1) The meaning of public information on covid-19 news by Batara pos media in Jalajja village, Burau district, East Luwu regency, The dominant position, relatively the same, namely: receiving information as a whole and starting to act. The position of negotiations, receiving the information but continuing to carry out their activities as usual because they understand the obligation to continue to comply with health protocols 2) The attitude of the community in responding to the news of covid-19 partly shows a positive attitude, namely not panicking when receiving the information and continuing to carry out activities as usual by applying health protocols. Other informants showed negative attitudes, namely, excessive panic and not controlling themselves so that it could harm people around them. A positive attitude shows a positive side and an ordinary expression and continues to carry out its activities as usual because of an obligation that needs to be carried out, a negative attitude shows a negative expression, that is, an excessive attitude by shutting yourself at home.